Co‐N‐Doped Mesoporous Carbon Hollow Spheres as Highly Efficient Electrocatalysts for Oxygen Reduction Reaction. Issue 3 (18th October 2016) - Hu, Feng; Yang, Hongchao; Wang, Changhong; Zhang, Yejun; Lu, Huan; Wang, Qiangbin
Abstract : Rational design of cost‐effective, nonprecious metal‐based catalysts with desirable oxygen reduction reaction (ORR) performance is extremely important for future fuel cell commercialization, etc. Herein, a new type of ORR catalyst of Co‐N‐doped mesoporous carbon hollow sphere (Co‐N‐mC) was developed by pyrolysis from elaborately fabricated polystyrene@polydopamine‐Co precursors. The obtained catalysts with active Co sites distributed in highly graphitized mesoporous N‐doped carbon hollow spheres exhibited outstanding ORR activity with an onset potential of 0.940 V, a half‐wave potential of 0.851 V, and a small Tafel slope of 45 mV decade −1 in 0.1m KOH solution, which was comparable to that of the Pt/C catalyst (20%, Alfa). More importantly, they showed superior durability with little current decline (less than 4%) in the chronoamperometric evaluation over 60 000 s. These features make the Co‐N‐mC one of the best nonprecious‐metal catalysts to date for ORR in alkaline condition. Abstract : A new type of oxygen reduction reaction (ORR) catalyst of Co‐N‐doped mesoporous carbon hollow sphere (Co‐N‐mC) is prepared by pyrolysis from elaborately fabricated polystyrene@polydopamine‐Co precursors. The obtained catalysts with active Co sites including coordinating Co moieties and Co nanoparticles distributed in highly graphitized mesoporous N‐doped carbon hollow spheres exhibit outstanding ORR activity and stability.